Polishing composition, polishing method, and method for producing semiconductor substrate
A polishing composition with abrasive grains of varying silanol group densities and a pH greater than 6 effectively polishes polycrystalline silicon doped with n-type impurities at a high speed, addressing the inefficiencies of existing technologies.
Patent Information
- Application Number
- JP2021049532
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-24
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2041-03-24
AI Technical Summary
There is a need for a polishing composition that can efficiently polish substrates containing polycrystalline silicon doped with n-type impurities at a high polishing speed, which has not been adequately addressed by existing technologies.
The polishing composition includes abrasive grains with specific silanol group densities, comprising first silica particles with a low silanol group density and second silica particles with a high silanol group density, combined with a dispersion medium and a pH greater than 6, allowing for effective polishing of polycrystalline silicon doped with n-type impurities.
This composition enables high-speed polishing of polycrystalline silicon doped with n-type impurities, improving the polishing efficiency and selectivity ratio compared to traditional methods.
Smart Images

Figure 0007663385000001 
Figure 0007663385000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a polishing composition, a polishing method, and a method for producing a semiconductor substrate. [Background technology]
[0002] In recent years, with the trend toward multi-layer wiring on the surface of semiconductor substrates, a so-called chemical mechanical polishing (CMP) technique is used to polish and flatten semiconductor substrates when manufacturing devices. CMP is a method for flattening the surface of an object to be polished (piece to be polished) such as a semiconductor substrate by using a polishing composition (slurry) containing abrasive grains such as silica, alumina, ceria, etc., an anticorrosive agent, a surfactant, etc., and the object to be polished (piece to be polished) is silicon, polysilicon, silicon oxide film (silicon oxide), silicon nitride, wiring, plugs, etc. made of metal, etc.
[0003] For example, as a technique for polishing a polysilicon film provided on a silicon substrate having an isolation region, Patent Document 1 discloses a polishing method including a step of performing preliminary polishing using a preliminary polishing composition containing abrasive grains, an alkali, a water-soluble polymer, and water, and a step of performing final polishing using a final polishing composition containing abrasive grains, an alkali, a water-soluble polymer, and water. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2007-103515 A Summary of the Invention [Problem to be solved by the invention]
[0005] Recently, substrates containing impurity-doped polycrystalline silicon (polysilicon) have come to be used as semiconductor substrates, and a new demand has arisen for polishing such substrates, but little research has been done on such demands.
[0006] SUMMARY OF THE PRESENT EMBODIMENTS Accordingly, an object of the present invention is to provide a means capable of polishing an object to be polished, which includes polycrystalline silicon doped with n-type impurities, at a high polishing rate. [Means for solving the problem]
[0007] In order to solve the above problems, the present inventors have conducted extensive research. As a result, the present inventors have discovered a polishing composition comprising an abrasive and a dispersion medium, the abrasive having a silanol group density of 0 particles / nm 2 More than 4 pieces / nm 2 and a first silica particle having a silanol group density of 4 / nm 2 More than 12 pieces / nm 2 The inventors have found that the above-mentioned problems can be solved by a polishing composition containing second silica particles having a pH of more than 6, and have completed the present invention. Effect of the Invention
[0008] According to the present invention, there is provided a polishing composition capable of polishing an object to be polished, which includes polycrystalline silicon doped with n-type impurities, at a high polishing rate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, the embodiments of the present invention will be described, but the present invention is not limited to only the following embodiments. Unless otherwise specified, the operation and measurement of physical properties are performed under the conditions of room temperature (20 to 25°C) and relative humidity 40 to 50% RH. In addition, in this specification, "X to Y" indicating a range means "X or more and Y or less."
[0010] <Polishing composition> The present invention relates to a polishing composition used for polishing an object to be polished, the polishing composition comprising an abrasive grain and a dispersion medium, the abrasive grain having a silanol group density of 0 particles / nm 2 More than 4 pieces / nm 2 and a first silica particle having a silanol group density of 4 / nm 2 More than 12 pieces / nm 2 and second silica particles having a pH of more than 6. The polishing composition of the present invention having such a configuration can polish an object to be polished including polycrystalline silicon doped with n-type impurities at a high polishing rate.
[0011] The reason why the polishing composition of the present invention exhibits the above-mentioned effects is not necessarily clear, but is thought to be as follows.
[0012] A polishing composition generally polishes an object to be polished by a physical action caused by rubbing the surface of a substrate, a chemical action caused by components other than the abrasive grains on the surface of the substrate, or a combination of these. Therefore, the shape and type of the abrasive grains have a large effect on the polishing rate.
[0013] The polishing composition of the present invention is an abrasive having a silanol group density of 0 particles / nm 2 More than 4 pieces / nm 2 The first silica particles have a silanol group density of 4 / nm or less (hereinafter, also referred to as "low silanol group density (first) silica particles"). 2 More than 12 pieces / nm 2and second silica particles (hereinafter also referred to as "(second) silica particles with high silanol group density"). That is, the polishing composition of the present invention contains two kinds of silica particles with different silanol group densities. Polycrystalline silicon (as well as polycrystalline silicon doped with n-type impurities) is highly hydrophobic. In general, the lower the silanol group density of the abrasive grains, the more hydrophobic they are, and the less bound water they are, and the easier it is to approach a hydrophobic object to be polished. In addition, the higher the silanol group density of the abrasive grains, the more hydrophilic they are, and the more bound water they are, and the harder it is to approach a hydrophobic film. Therefore, during polishing, the first silica particles with low silanol group density contained in the polishing composition can approach the object to be polished and sufficiently apply mechanical force to the object to be polished (polished surface), and can be polished suitably. During polishing, the second silica particles with high silanol group density contained in the polishing composition are present at a position away from the polished surface, and serve to press the first silica particles against the object to be polished. In other words, the second silica particles further strengthen the mechanical force applied to the object to be polished by the first silica particles, and polishing can be performed with stronger force. In other words, the present invention has found a combination of abrasive grains that can effectively act on the polishing surface.
[0014] The polishing composition of the present invention has a pH exceeding 6. The polishing composition of the present invention, which is used to polish an object containing polycrystalline silicon doped with n-type impurities, has a pH exceeding 6, which allows the polycrystalline silicon doped with n-type impurities to be polished efficiently, and therefore the effect of the above-mentioned abrasive grain configuration is considered to be exerted as a more significant effect.
[0015] As described above, it is believed that because the first and second silica particles have relatively low and high silanol group densities, respectively, the two types of abrasive grains with different adsorptivities to the object to be polished can impart different effects to the object to be polished, thereby improving the polishing rate.
[0016] Furthermore, the present inventors have found that when there are first silica particles approaching the polishing object and second silica particles present at a position farther away from the polishing object than the first silica particles (i.e., when there are silica particles with a low silanol group density and silica particles with a high silanol group density), the effect of the present invention (high polishing rate) is further improved by the difference in particle size of the two types of silica particles. The second silica particles impart a force (a force pressing against the polishing object) to the first silica particles so that the first silica particles can impart a strong mechanical force to the polishing object. In this case, the larger the particle diameter, the stronger the pressing force. Also, the smaller the particle diameter of the first silica particles that polish the polishing object, the smaller the area of contact with the polishing surface, and the higher the energy density imparted to the polishing surface. Therefore, it has been found that the polishing rate is further improved by the average secondary particle diameter of the first silica particles approaching the polishing object being relatively small and the average secondary particle diameter of the second silica particles present at a position farther away from the polishing object being relatively large.
[0017] As described above, in the polishing composition of the present invention, the first silica particles and the second silica particles, which are arranged at different positions relative to the object to be polished during polishing, have relatively different particle sizes, and therefore the polishing properties of the polishing composition are further improved. However, it goes without saying that such a mechanism is merely speculation and does not limit the technical scope of the present invention.
[0018] [Polished object] The object to be polished according to the present invention includes a polycrystalline silicon (polysilicon) film doped with n-type impurities. That is, the object to be polished according to the present invention is used for polishing an object to be polished that includes a polycrystalline silicon film doped with n-type impurities.
[0019] Examples of n-type impurities that can be doped into polycrystalline silicon include elements of Group 15 such as phosphorus (P), arsenic (As), bismuth (Bi), antimony (Sb), etc. Among these n-type impurities, phosphorus is preferred.
[0020] The lower limit of the content (doping amount) of n-type impurities doped into polycrystalline silicon is not particularly limited, but is preferably 1 at% or more, more preferably 2.5 at% or more, and even more preferably 5 at% or more, relative to the total of 100 at% of polycrystalline silicon and impurities. The upper limit of the content (doping amount) of n-type impurities doped into polycrystalline silicon is not particularly limited, but is preferably 50 at% or less, more preferably 30 at% or less, and even more preferably 25 at% or less, relative to the total of 100 at% of polycrystalline silicon and impurities. The content of n-type impurities doped into polycrystalline silicon is calculated using a multifunction scanning X-ray photoelectron spectroscopy analyzer (XPS) by the method described in the examples below.
[0021] The object to be polished according to the present invention may contain other materials in addition to the polycrystalline silicon (polysilicon) film doped with n-type impurities. Examples of other materials include silicon nitride (SiN), silicon carbonitride (SiCN), silicon oxide, undoped polycrystalline silicon (undoped polysilicon), undoped amorphous silicon (undoped amorphous silicon), metal, SiGe, etc.
[0022] Examples of films containing silicon oxide include, for example, TEOS (Tetraethyl Orthosilicate) type silicon oxide films (hereinafter, simply referred to as "TEOS films") produced using tetraethyl orthosilicate as a precursor, HDP (High Density Plasma) films, USG (Undoped Silicate Glass) films, PSG (Phosphorus Silicate Glass) films, BPSG (Boron-Phospho Silicate Glass) films, and RTO (Rapid Thermal Oxidation (CO) films and the like.
[0023] Examples of the metal include tungsten, copper, aluminum, cobalt, hafnium, nickel, gold, silver, platinum, palladium, rhodium, ruthenium, iridium, and osmium.
[0024] The object to be polished according to the present invention preferably further comprises a silicon oxide film or a silicon nitride film, more preferably further comprises a silicon oxide film.Therefore, the polishing composition of the present invention is preferably used for polishing an object to be polished that includes a polycrystalline silicon (polysilicon) film doped with n-type impurities and a silicon oxide film or a silicon nitride film, and more preferably used for polishing an object to be polished that includes a polycrystalline silicon (polysilicon) film doped with n-type impurities and a silicon oxide film.
[0025] In one embodiment, the polishing object of the present invention further includes at least one of a silicon oxide film (preferably a TEOS film) and a silicon nitride film in addition to the polycrystalline silicon film doped with n-type impurities. When the polishing composition of the present invention polishes a silicon oxide film (preferably a TEOS film) and / or a silicon nitride film together with the polycrystalline silicon film doped with n-type impurities, the polishing composition of the present invention can selectively polish the polycrystalline silicon film doped with n-type impurities. That is, even when polishing an object to be polished that includes a polycrystalline silicon film doped with n-type impurities and a silicon oxide film (preferably a TEOS film) and / or a silicon nitride film, the polishing composition of the present invention can selectively polish the polycrystalline silicon film doped with n-type impurities at a high polishing rate. Therefore, it is possible to obtain the effect of maintaining or suppressing the polishing speed of a silicon oxide film (preferably a TEOS film) and / or a silicon nitride film while improving the polishing speed of a polycrystalline silicon film doped with n-type impurities, i.e., the effect of improving the ratio (selectivity) of the polishing speed of a polycrystalline silicon film doped with n-type impurities to the polishing speed of a silicon oxide film and / or a silicon nitride film.
[0026] In one embodiment, the object to be polished of the present invention can improve the polishing rate of a polycrystalline silicon film doped with n-type impurities while improving the polishing rate of a silicon oxide film (preferably a TEOS film) and / or a silicon nitride film, and can improve the ratio (selectivity) of the polishing rate of a polycrystalline silicon film doped with n-type impurities to the polishing rate of a silicon oxide film and / or a silicon nitride film. Such a polishing composition having a high polishing rate of a silicon oxide film (preferably a TEOS film) and / or a silicon nitride film is preferable because it can maintain a high polishing rate without decreasing the polishing rate even when a natural oxide film is formed.
[0027] [Abrasive grain] The polishing composition of the present invention contains abrasive grains. In the polishing composition of the present invention, the abrasive grains have a silanol group density of 0 particles / nm 2 More than 4 pieces / nm 2 and a first silica particle having a silanol group density of 4 / nm 2 More than 12 pieces / nm 2 and a second silica particle having the following structure. In one embodiment, the abrasive grain is composed of a first silica particle and a second silica particle. In this specification, "silanol group density" refers to the number of silanol groups per unit area of the silica particle surface. The silanol group density is an index for expressing the electrical or chemical properties of the silica particle surface.
[0028] In this specification, the silanol group density is calculated based on the specific surface area measured by the BET method and the amount of silanol groups measured by titration. For example, the average silanol group density (unit: silanol group / nm2) on the surface of silica (polishing grain) was determined by the Sears titration method using neutralization titration described in "Analytical Chemistry, vol. 28, No. 12, 1956, 1982-1983" by GW Sears. 2) can be calculated. The "Sears titration method" is an analytical method commonly used by colloidal silica manufacturers to evaluate silanol group density, and is a calculation method based on the amount of sodium hydroxide solution required to change the pH from 4 to 9. Details of silanol group density measurement are described in detail in the Examples below.
[0029] In one embodiment of the present invention, the number of silanol groups per unit surface area of the abrasive grain is set to 0 / nm 2 More than 4 pieces / nm 2 or less, or 4 pieces / nm 2 More than 12 pieces / nm 2 In order to achieve the above, it is effective to select a manufacturing method for the abrasive grains, and for example, it is preferable to carry out a heat treatment such as calcination. In one embodiment of the present invention, calcination is carried out, for example, by holding the abrasive grains (e.g., silica) in an environment of 120 to 200°C for 30 minutes or more. By carrying out such a heat treatment, the number of silanol groups on the abrasive grain surface can be reduced to 0 groups / nm 2 More than 4 pieces / nm 2 or less, or 4 pieces / nm 2 More than 12 pieces / nm 2 By carrying out such a special treatment, the number of silanol groups on the abrasive grain surface can be reduced to a desired value such as 0 / nm2 or less. 2 More than 4 pieces / nm 2 or less, or 4 pieces / nm 2 More than 12 pieces / nm 2 It can be as follows:
[0030] The silanol group density of the first silica particles is preferably 0.5 / nm 2 More than 4 pieces / nm 2 More preferably, it is 0.6 particles / nm 2 More than 3.8 pieces / nm 2 More preferably, the number is 0.8 / nm 2 More than 3.6 pieces / nm 2 or less, and particularly preferably 0.9 particles / nm 2 More than 3.5 pieces / nm 2 or less, and most preferably 1 / nm 2More than 3 pieces / nm 2 When the silanol group density of the first silica particles is within the above range, the first silica particles can approach the object to be polished during polishing, and the mechanical force of the first silica particles can be effectively applied to the object to be polished.
[0031] The silanol group density of the second silica particles is preferably 4.5 / nm 2 More than 12 pieces / nm 2 More preferably, 5 / nm 2 More than 12 pieces / nm 2 More preferably, 5.5 particles / nm 2 More than 12 pieces / nm 2 or less, and particularly preferably 6 / nm 2 More than 12 pieces / nm 2 or less, and most preferably 6 / nm 2 Exceeds 11.5 particles / nm 2 When the silanol group density of the second silica particles is within the above range, the second silica particles are positioned farther from the object to be polished than the first silica particles during polishing, and the force of the second silica particles (the force pressing the second silica particles toward the object to be polished) is effectively applied to the first silica particles.
[0032] The first silica particle and the second silica particle are more preferably colloidal silica.The colloidal silica can be produced by the sodium silicate method or the sol-gel method, and the colloidal silica produced by any method can be suitably used as the first silica particle and the second silica particle of the present invention.However, from the viewpoint of reducing metal impurities, the colloidal silica produced by the sol-gel method is preferred because it can be produced with high purity.
[0033] Furthermore, the first silica particles and the second silica particles may each be surface-modified as long as the silanol group density satisfies the above range. For example, the first silica particles and the second silica particles may be colloidal silica with an organic acid fixed thereto. The organic acid is fixed to the surface of the colloidal silica contained in the polishing composition by, for example, chemically bonding a functional group of the organic acid to the surface of the colloidal silica. The organic acid is not fixed to the colloidal silica by simply allowing the colloidal silica and the organic acid to coexist. If sulfonic acid, which is a type of organic acid, is to be fixed to the colloidal silica, it can be performed by, for example, the method described in “Sulfonic acid-functionalized silica through quantitative oxidation of thiol groups”, Chem. Commun. 246-247 (2003). Specifically, a silane coupling agent having a thiol group such as 3-mercaptopropyltrimethoxysilane is coupled to the colloidal silica, and then the thiol group is oxidized with hydrogen peroxide to obtain colloidal silica with a sulfonic acid fixed to the surface. Alternatively, when a carboxylic acid is immobilized on colloidal silica, it can be carried out by, for example, the method described in “Novel Silane Coupling Agents Containing a Photolabile 2-Nitrobenzyl Ester for Introduction of a Carboxy Group on the Surface of Silica Gel”, Chemistry Letters, 3, 228-229 (2000). Specifically, a silane coupling agent containing a photoreactive 2-nitrobenzyl ester is coupled to colloidal silica, and then the resulting mixture is irradiated with light to obtain colloidal silica having a carboxylic acid immobilized on the surface.
[0034] In the polishing composition of the present invention, the abrasive grains may contain abrasive grains other than the first silica particles and the second silica particles (hereinafter, other abrasive grains). The type of other abrasive grains contained in the polishing composition of the present invention is not particularly limited, and may include, for example, oxides such as silica, alumina, zirconia, titania, etc. other than the first silica particles and the second silica particles. The other abrasive grains may be used alone or in combination of two or more kinds. The other abrasive grains may be commercially available products or synthetic products.
[0035] In the following description, when referring to "abrasive grains," that is, first silica particles, second silica particles, and other abrasive grains are referred to without distinction, unless otherwise specified.
[0036] The lower limit of the average primary particle size of the first silica particles is preferably 5 nm or more, more preferably 7 nm or more, even more preferably 10 nm or more, particularly preferably 15 nm or more, and most preferably 20 nm or more.The upper limit of the average primary particle size of the first silica particles is preferably 300 nm or less, more preferably 250 nm or less, even more preferably 200 nm or less, particularly preferably 180 nm or less, and most preferably 150 nm or less.Within such a range, the polishing speed for the polishing object can be further improved.
[0037] The lower limit of the average primary particle size of the second silica particles is preferably 10nm or more, more preferably 15nm or more, even more preferably 20nm or more, particularly preferably 25nm or more, and most preferably 30nm or more.The upper limit of the average primary particle size of the second silica particles is preferably 400nm or less, more preferably 300nm or less, even more preferably 250nm or less, particularly preferably 200nm or less, and most preferably 180nm or less.Within such a range, the polishing speed for the polishing object can be further improved.
[0038] The average primary particle size of the abrasive grains can be calculated based on the specific surface area measured using the BET method.
[0039] The lower limit of the average secondary particle diameter of the first silica particles is preferably 10 nm or more, more preferably 20 nm or more, even more preferably 30 nm or more, particularly preferably 40 nm or more, and most preferably 50 nm or more. The upper limit of the average secondary particle diameter of the first silica particles is preferably 200 nm or less, more preferably 180 nm or less, even more preferably 150 nm or less, particularly preferably 100 nm or less, and most preferably 80 nm or less. That is, the average secondary particle diameter of the first silica particles is preferably 10 nm or more and 200 nm or less, more preferably 20 nm or more and 180 nm or less, even more preferably 30 nm or more and 150 nm or less, particularly preferably 40 nm or more and 100 nm or less, and most preferably 10 nm or more and 80 nm or less. Within such a range, the polishing speed for the polishing object can be further improved.
[0040] The lower limit of the average secondary particle diameter of the second silica particles is preferably 20 nm or more, more preferably 40 nm or more, even more preferably 50 nm or more, particularly preferably 80 nm or more, and most preferably 100 nm or more. The upper limit of the average secondary particle diameter of the second silica particles is preferably 300 nm or less, more preferably 280 nm or less, even more preferably 250 nm or less, particularly preferably 200 nm or less, and most preferably 180 nm or less. That is, the average secondary particle diameter of the second silica particles is preferably 20 nm or more and 300 nm or less, more preferably 40 nm or more and 280 nm or less, even more preferably 50 nm or more and 250 nm or less, particularly preferably 80 nm or more and 200 nm or less, and most preferably 100 nm or more and 180 nm or less. Within such a range, the polishing speed for the polishing object can be further improved.
[0041] In one embodiment of the present invention, the average secondary particle size of the first silica particles is smaller than the average secondary particle size of the second silica particles, thereby further improving the polishing rate with the polishing composition.
[0042] In one embodiment of the present invention, the average secondary particle diameter of the first silica particles is smaller than that of the second silica particles, the average secondary particle diameter of the first silica particles is 10 nm or more and 200 nm or less, and the average secondary particle diameter of the second silica particles is 20 nm or more and 300 nm or less, thereby further improving the polishing rate by the polishing composition.
[0043] The average secondary particle diameter of the abrasive grains can be measured, for example, by a dynamic light scattering method such as a laser diffraction scattering method. That is, the average secondary particle diameter of the abrasive grains corresponds to the diameter D50 of the particles when the cumulative particle mass from the fine particle side reaches 50% of the total particle mass in the particle size distribution of the abrasive grains determined by the laser diffraction scattering method.
[0044] The average degree of association of the abrasive grains is preferably 4.0 or less, more preferably 3.0 or less, and even more preferably 2.5 or less. As the average degree of association of the abrasive grains decreases, the occurrence of defects on the surface of the object to be polished can be further reduced. In addition, the average degree of association of the abrasive grains is preferably 1.5 or more, more preferably 1.8 or more. As the average degree of association of the abrasive grains increases, there is an advantage that the polishing rate by the polishing composition improves. The average degree of association of the abrasive grains is obtained by dividing the value of the average secondary particle diameter of the abrasive grains by the value of the average primary particle diameter.
[0045] The size of the abrasive grains (eg, average particle diameter) can be appropriately controlled by selecting the manufacturing method of the abrasive grains.
[0046] The lower limit of the content (concentration) of the abrasive grains in the polishing composition according to one embodiment of the present invention is preferably 0.2 mass% or more, more preferably 0.3 mass% or more, and even more preferably 0.5 mass% or more, based on the polishing composition. The upper limit of the content of the abrasive grains in the polishing composition according to the present invention is preferably 20 mass% or less, more preferably 15 mass% or less, more preferably 10 mass% or less, and even more preferably 5 mass% or less, based on the polishing composition. In such a range, the polishing rate can be further improved. In addition, when the polishing composition contains two or more kinds of abrasive grains, the content of the abrasive grains means the total amount of these.
[0047] In one embodiment of the present invention, the mass ratio of the first silica particles to the second silica particles is preferably 1:10 to 10:1, more preferably 1:5 to 5:1, and even more preferably 1:2 to 2:1. Within such a range, the polishing rate can be further improved.
[0048] [Polishing speed enhancer] In one embodiment, the polishing composition of the present invention further comprises at least one polishing rate enhancer selected from the group consisting of aminoethylpiperazine and ammonia. Here, the polishing rate enhancer refers to a compound that has the function of improving the polishing rate of the polishing composition by being added to the polishing composition. The polishing rate enhancer has the function of chemically polishing the surface of the object to be polished and the function of improving the dispersion stability of the polishing composition. In addition, the polishing rate enhancer contained in the polishing composition of the present invention has the effect of increasing the electrical conductivity of the polishing composition. It is believed that this further improves the polishing rate by the polishing composition.
[0049] In an embodiment of the present invention, the lower limit of the content of the polishing rate enhancer in the polishing composition is preferably 0.001% by mass or more, more preferably 0.05% by mass or more, even more preferably 0.01% by mass or more, particularly preferably 0.05% by mass or more, and most preferably 0.07% by mass or more, based on the polishing composition. By having such a lower limit, the polishing rate is further improved. The upper limit of the content of the polishing rate enhancer in the polishing composition is preferably 10% by mass or less, more preferably 8% by mass or less, even more preferably 5% by mass or less, particularly preferably 3% by mass or less, and most preferably 1% by mass or less, based on the polishing composition. By having such an upper limit, a stable slurry without aggregation can be obtained.
[0050] [pH and pH adjusters] The pH of the polishing composition of the present invention is more than 6. If the pH is 6 or less, the polishing rate of the polishing object cannot be improved. The pH of the polishing composition of the present invention may be more than 6, but is preferably pH 7 or more, more preferably pH 7.5 or more, even more preferably pH 8 or more, even more preferably pH 9 or more, particularly preferably pH 9.5 or more, and most preferably pH 10 or more. If the pH is more than 6, even when polishing an object to be polished that includes polycrystalline silicon doped with n-type impurities and a silicon oxide film (preferably a TEOS film) and / or a silicon nitride film, the polycrystalline silicon doped with n-type impurities can be selectively polished at a high polishing rate. The upper limit of the pH is preferably 13 or less, more preferably 12.5 or less, in practical terms.
[0051] The polishing composition of the present invention may further contain a pH adjuster, if necessary. The pH adjuster adjusts the pH of the polishing composition to a desired value.
[0052] The pH adjuster contained in the polishing composition of the present invention includes inorganic acids, organic acids, alkalis, etc. These may be used alone or in combination of two or more.
[0053] Specific examples of inorganic acids that can be used as pH adjusters include hydrochloric acid, sulfuric acid, nitric acid, hydrofluoric acid, boric acid, carbonic acid, hypophosphorous acid, phosphorous acid, and phosphoric acid. Among these, hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid are preferred.
[0054] Specific examples of organic acids that can be used as pH adjusters include formic acid, acetic acid, propionic acid, butyric acid, valeric acid, 2-methylbutyric acid, n-hexanoic acid, 3,3-dimethylbutyric acid, 2-ethylbutyric acid, 4-methylpentanoic acid, n-heptanoic acid, 2-methylhexanoic acid, n-octanoic acid, 2-ethylhexanoic acid, benzoic acid, glycolic acid, salicylic acid, glyceric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, maleic acid, phthalic acid, malic acid, tartaric acid, citric acid, lactic acid, diglycolic acid, 2-furan carboxylic acid, 2,5-furandicarboxylic acid, 3-furan carboxylic acid, 2-tetrahydrofuran carboxylic acid, methoxyacetic acid, methoxyphenylacetic acid, and phenoxyacetic acid. Organic sulfuric acids such as methanesulfonic acid, ethanesulfonic acid, and isethionic acid may also be used. Among these, dicarboxylic acids such as malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, maleic acid, phthalic acid, malic acid and tartaric acid, and tricarboxylic acids such as citric acid are preferred.
[0055] Instead of or in combination with an inorganic or organic acid, a salt such as an alkali metal salt of an inorganic or organic acid may be used as a pH adjuster. In the case of a combination of a weak acid and a strong base, a strong acid and a weak base, or a weak acid and a weak base, a pH buffering effect can be expected.
[0056] Specific examples of alkalis that can be used as pH adjusters include ammonia, sodium hydroxide, potassium hydroxide, tetramethylammonium hydroxide, etc. The content of the pH adjuster can be selected by appropriately adjusting it within the range in which the effects of the present invention can be achieved.
[0057] In one embodiment of the present invention, the polishing composition further comprises a pH adjuster, and the pH adjuster comprises potassium hydroxide. By including potassium hydroxide in the pH adjuster, the electrical conductivity can be easily adjusted to a preferred range, which has the advantageous effect of further improving the polishing rate.
[0058] The pH of the polishing composition can be measured by, for example, a pH meter.Specifically, using a pH meter (for example, Horiba, Ltd., model number: LAQUA) or the like, perform three-point calibration using standard buffer (phthalate pH buffer pH: 4.01 (25°C), neutral phosphate pH buffer pH: 6.86 (25°C), carbonate pH buffer pH: 10.01 (25°C)), then put a glass electrode into the polishing composition, and measure the value after 2 minutes or more have passed and the pH of the polishing composition is stabilized.
[0059] [Dispersion medium] The polishing composition of the present invention contains a dispersion medium for dispersing each component. Examples of the dispersion medium include water; alcohols such as methanol, ethanol, and ethylene glycol; ketones such as acetone, and mixtures thereof. Of these, water is preferred as the dispersion medium. That is, according to a preferred embodiment of the present invention, the dispersion medium contains water. According to a more preferred embodiment of the present invention, the dispersion medium is substantially composed of water. Note that the above "substantially" means that a dispersion medium other than water may be included as long as the objective effect of the present invention can be achieved, and more specifically, the dispersion medium is preferably composed of 90% by mass or more and 100% by mass or less of water and 0% by mass or more and 10% by mass or less of a dispersion medium other than water, and more preferably composed of 99% by mass or more and 100% by mass or less of water and 0% by mass or more and 1% by mass or less of a dispersion medium other than water. Most preferably, the dispersion medium is water.
[0060] From the viewpoint of not inhibiting the action of the components contained in the polishing composition, it is preferable for the dispersion medium to be water that contains as few impurities as possible. Specifically, pure water or ultrapure water from which impurity ions have been removed with an ion exchange resin and then foreign matter has been removed through a filter, or distilled water is more preferable.
[0061] [Other ingredients] The polishing composition of the present invention may further contain known additives that can be used in polishing compositions, such as complexing agents, preservatives, and antifungal agents, as necessary, within the scope of not significantly impairing the effects of the present invention. However, according to an embodiment of the present invention, the polishing composition does not substantially contain an oxidizing agent. According to such an embodiment, even when polishing an object to be polished that includes polycrystalline silicon doped with n-type impurities and a silicon oxide film (preferably a TEOS film) and / or a silicon nitride film, it is possible to selectively polish polycrystalline silicon doped with n-type impurities at a high polishing rate. Note that "substantially free" includes the concept of not being contained at all in the polishing composition, as well as the case where the polishing composition contains 0.1 mass % or less.
[0062] [Electrical Conductivity of Polishing Composition] The lower limit of the electrical conductivity of the polishing composition of the present invention is preferably 0.1 mS / cm or more, more preferably 0.3 mS / cm or more, even more preferably 0.5 mS / cm or more, particularly preferably 0.8 mS / cm or more, and most preferably 0.9 mS / cm or more. The upper limit of the electrical conductivity of the polishing composition of the present invention is preferably 6 mS / cm or less, more preferably 5 mS / cm or less, even more preferably 4.5 mS / cm or less, particularly preferably 4 mS / cm or less, and most preferably 3.5 mS / cm or less. By having the electrical conductivity of the polishing composition in the above range, there is an advantageous effect of further improving the polishing rate. The electrical conductivity of the polishing composition is a value measured by a tabletop electrical conductivity meter (manufactured by Horiba, Ltd., model number: DS-71).
[0063] [Method of manufacturing the polishing composition] The method for producing the polishing composition of the present invention is not particularly limited, and can be obtained, for example, by stirring and mixing abrasive grains and other components as necessary in a dispersion medium (for example, water). The details of each component are as described above.
[0064] The temperature at which the components are mixed is not particularly limited, but is preferably 10° C. to 40° C., and may be heated to increase the dissolution rate. The mixing time is also not particularly limited as long as the components can be mixed uniformly.
[0065] [Polishing method and semiconductor substrate manufacturing method] As described above, the polishing composition of the present invention is suitable for use in polishing an object to be polished that includes a polycrystalline silicon film doped with n-type impurities. Thus, the present invention provides a polishing method for polishing an object to be polished that includes a polycrystalline silicon film doped with n-type impurities with the polishing composition of the present invention. That is, the present invention includes a polishing method comprising a step of polishing an object to be polished that includes a polycrystalline silicon film doped with n-type impurities using the polishing composition of the present invention. The present invention also provides a method for producing a semiconductor substrate that comprises a step of polishing a semiconductor substrate that includes a polycrystalline silicon film doped with n-type impurities by the polishing method.
[0066] As a polishing device, a general polishing device can be used that is equipped with a holder for holding a substrate or the like having an object to be polished, a motor whose rotation speed can be changed, and a polishing platen onto which a polishing pad (polishing cloth) can be attached.
[0067] The polishing pad may be made of any material, including general nonwoven fabric, polyurethane, porous fluororesin, etc. It is preferable that the polishing pad has grooves formed thereon to allow the polishing liquid to accumulate.
[0068] Regarding the polishing conditions, for example, the rotation speed of the polishing platen was 10 rpm (0.17 s -1 ) or more 500rpm(8.3s -1 ) or less. The pressure (polishing pressure) applied to the substrate having the object to be polished is preferably 0.5 psi (3.4 kPa) or more and 10 psi (68.9 kPa) or less. The method of supplying the polishing composition to the polishing pad is not particularly limited, and for example, a method of continuously supplying the composition using a pump or the like is used. There is no limit to the amount of supply, but it is preferable that the surface of the polishing pad is always covered with the polishing composition of the present invention.
[0069] After polishing, the substrate is washed with running water, and water droplets adhering to the substrate are removed by a spin dryer or the like, followed by drying to obtain a substrate having a metal-containing layer.
[0070] The polishing composition of the present invention may be a one-liquid type or a multi-liquid type such as a two-liquid type. The polishing composition of the present invention may be prepared by diluting the stock solution of the polishing composition, for example, 10 times or more, with a diluent such as water.
[0071] [Polishing speed] In the present invention, the polishing speed of the polycrystalline silicon film doped with n-type impurities is preferably 1000 Å / min to 7000 Å / min, more preferably 1200 Å / min to 6800 Å / min, even more preferably 1500 Å / min to 6500 Å / min, and particularly preferably 2000 Å / min to 6000 Å / min. The polishing speed of the silicon oxide film (preferably the TEOS film) and / or the silicon nitride film is preferably 15 Å / min to 500 Å / min, more preferably 20 Å / min to 300 Å / min, even more preferably 25 Å / min to 250 Å / min, and particularly preferably 50 Å / min to 200 Å / min.
[0072] [Selection ratio] The selectivity is calculated by dividing the polishing speed (Å / min) of a polycrystalline silicon film doped with n-type impurities (P'poly-Si) by the polishing speed (Å / min) of a silicon oxide film (TEOS) and / or a silicon nitride film (SiN). In the present invention, the selectivity (P'poly-Si / (TEOS or SiN) is preferably 10 or more and 50 or more, more preferably 11 or more and 45 or less, and even more preferably 15 or more and 40 or more. EXAMPLES
[0073] The present invention will be described in more detail using the following examples and comparative examples. However, the technical scope of the present invention is not limited to the following examples. Unless otherwise specified, "%" and "parts" mean "% by mass" and "parts by mass", respectively. In the following examples, unless otherwise specified, the operations were performed under the conditions of room temperature (20 to 25°C) / relative humidity 40 to 50% RH.
[0074] [Preparation of abrasive grains] (Preparation of First Silica Particles and Second Silica Particles) As the first silica particles and the second silica particles, silica particles having the silanol group density shown in Table 1 were prepared. That is, the first silica particles and the second silica particles are prepared by, for example, holding the silica in an environment of 120 to 200° C. for 30 minutes or more and baking the silica, thereby reducing the number of silanol groups on the silica particle surface to 0 / nm 2 More than 4 pieces / nm 2 or less, or 4 pieces / nm 2 More than 12 pieces / nm 2 The values were adjusted to the desired values, such as: Silica particle A: silanol group density 1.6 particles / nm 2 , average primary particle size: 30nm, average secondary particle size: 60nm, average degree of association: 2 Silica particle B: silanol group density 3.5 particles / nm 2 , average primary particle size: 30nm, average secondary particle size: 60nm, average degree of association: 2 Silica particle C: silanol group density 7.9 particles / nm 2 , average primary particle size: 90nm, average secondary particle size: 210nm, average degree of association: 2.3 Silica particle d: silanol group density 6.57 / nm 2 , average primary particle size: 78 nm, average secondary particle size: 120 nm, average degree of association: 1.6 Silica particle e: silanol group density 5.7 particles / nm 2 , average primary particle size: 35 nm, average secondary particle size: 70 nm, average degree of association: 2 The silanol group density (unit: particle / nm 2) was calculated by the following method after measuring and calculating each parameter by the following measurement and calculation methods.
[0075] [Calculation method for silanol group density] The silanol group densities of the first and second silica particles were calculated by the Sears method using neutralization titration described in Analytical Chemistry, vol. 28, No. 12, 1956, 1982-1983 by GW Sears.
[0076] More specifically, the silanol group density of the first silica particles and the second silica particles was calculated by the following formula 1 by titrating the first silica particles and the second silica particles as measurement samples using the above-mentioned method.
[0077] ρ = (c × V × N A ×10 -21 ) / (C×S)...Equation 1 In the above formula 1, ρ is the silanol group density (pcs / nm 2 ) ; c represents the concentration (mol / L) of the sodium hydroxide solution used in the titration; V represents the volume (L) of sodium hydroxide solution required to raise the pH from 4.0 to 9.0; N A represents the Avogadro constant (units / mol); S represents the BET specific surface area (nm / g) of the silica particles.
[0078] [Particle size of first silica particles and second silica particles] The average primary particle size of the abrasive grains (first and second silica particles) was calculated from the specific surface area of the abrasive grains measured by the BET method using a Micromeritics "Flow SorbII 2300" and the density of the abrasive grains. The average secondary particle size of the abrasive grains (first and second silica particles) was measured using a Nikkiso Co., Ltd. dynamic light scattering particle size and particle size distribution analyzer UPA-UTI151.
[0079] [Preparation of polishing composition] Example 1 The first silica particles obtained above were used as abrasive grains: silica particles a (silanol group density 1.6 / nm 2 , average primary particle diameter: 30 nm, average secondary particle diameter: 60 nm, average degree of association: 2) and the second silica particle: silica particle c (silanol group density 7.9 pieces / nm 2 A mixture was obtained by adding 1% by mass and 1.5% by mass of the above-mentioned polyaniline (average primary particle size: 90 nm, average secondary particle size: 210 nm, average degree of association: 2.3) and aminoethylpiperazine as a polishing accelerator to final concentrations of 0.02% by mass to pure water as a dispersion medium at room temperature (25°C).
[0080] Thereafter, potassium hydroxide was added as a pH adjuster to the mixture so that the pH was 11, and the mixture was stirred and mixed at room temperature (25°C) for 30 minutes to prepare a polishing composition. The pH of the polishing composition (liquid temperature: 25°C) was confirmed with a pH meter (manufactured by Horiba Ltd., model number: LAQUA). The electrical conductivity of the polishing composition was measured with a tabletop electrical conductivity meter (manufactured by Horiba Ltd., model number: DS-71).
[0081] (Examples 2 to 11, Comparative Examples 1 to 8) Polishing compositions of Examples 2 to 11 and Comparative Examples 1 to 8 were prepared in the same manner as in Example 1, except that the type and content of the first and second silica particles, the type and content of the polishing accelerator, and the pH (type and content of the pH adjuster) were changed as shown in Table 1 below. In Table 1 below, "-" indicates that the agent was not contained. The pH and electrical conductivity of each obtained polishing composition, and the average secondary particle size of the abrasive grains (first and second silica particles) in each polishing composition are shown in Table 1 below.
[0082] In Table 1, the "particle size" of the first and second silica particles represents the average secondary particle size, "AEP" in the polishing rate enhancer column represents aminoethylpiperazine, "EC" represents electrical conductivity, "P'poly-Si" in the polishing rate column represents phosphorus-doped polysilicon, and "P'poly-Si / TEOS" in the selectivity column represents the selectivity of the phosphorus-doped polysilicon film to the TEOS film. Note that "P'poly-Si / TEOS" is calculated by dividing the polishing rate of P'poly-Si by the polishing rate of TEOS.
[0083] The particle diameters (average primary particle diameter, average secondary particle diameter) of the abrasive grains in the polishing composition were similar to those of the powdered abrasive grains. The method for measuring the particle diameters was the same as that described above. Here, in the present invention, a polishing composition containing first silica particles as abrasive grains was prepared (the composition other than the abrasive grains was the same), and the particle diameters of the first silica particles in the polishing composition were measured. The same was also performed for the second silica particles. This confirmed that the particle diameters (average primary particle diameter, average secondary particle diameter) of the first and second silica particles in the polishing composition were similar to those of the powdered first and second silica particles, respectively.
[0084] [Evaluation of polishing speed] Each of the polishing compositions obtained above was used to measure the removal rate when polishing the following object to be polished under the following polishing conditions.
[0085] (Polishing equipment and polishing conditions) Polishing equipment: Engis Japan Co., Ltd. Lapping machine EJ-380IN-CH Polishing pad: Nitta DuPont hard polyurethane pad IC1010 Polishing pressure: 3.0 psi (1 psi = 6894.76 Pa) Polishing platen rotation speed: 60 rpm Head (carrier) rotation speed: 60 rpm Supply of polishing composition: free-flowing Polishing composition supply amount: 100mL / min Polishing time: 30 seconds.
[0086] (Object to be polished) A 300 mm blanket wafer with a 3000 Å thick phosphorus-doped polysilicon film (phosphorus content: 20 at%) on its surface was prepared as the polishing target. A silicon wafer (300 mm, blanket wafer, manufactured by Advantec Co., Ltd.) with a 10000 Å thick TEOS film formed on its surface was also prepared as the polishing target. The wafer was then cut into 30 mm x 30 mm chip coupons, which were used as test pieces for the polishing test. Details of the polishing target used in the test are shown below.
[0087] The impurity content (doping amount) is the amount relative to the total of polysilicon and impurities, which is 100 at %. The content of n-type impurities doped into polycrystalline silicon is calculated under the following conditions using the following equipment.
[0088] Measuring equipment: Multi-function scanning X-ray photoelectron spectroscopy (XPS) Equipment name and manufacturer: PHI5000 Versa Probe, manufactured by ULVAC-PHI, Inc. Measurement: In the case of phosphorus-doped polysilicon, the measurement elements were four types: phosphorus, silicon, oxygen, and carbon. The number of sweeps of the measurement device was 10 for each element. The output value of the polysilicon (Poly-Si output value; i.e., the total output value of Si, O, and C) and the output value of phosphorus (P output value) were used to calculate the phosphorus content (P content) (at%) relative to the total of polysilicon and phosphorus (100 at%) according to the following formula 2.
[0089] P content (at%) =P output value (%) / (Poly-Si output value (%)+P output value (%))···Equation 2.
[0090] (polishing speed) The removal rate (RR) was calculated according to the following formula.
[0091]
number
[0092] The film thickness was measured using an optical interference film thickness measuring device (manufactured by Dainippon Screen Mfg. Co., Ltd., model number: Lambda Ace VM-2030), and the polishing rate was evaluated by dividing the difference in film thickness before and after polishing by the polishing time.
[0093] The evaluation results of the polishing rates for the phosphorus-doped polysilicon film and the TEOS film are shown in Table 1 below.
[0094] [Table 1]
[0095] As shown in Table 1, when the polishing compositions of Examples 1 to 11 were used, the polishing rate for the phosphorus-doped polysilicon film exceeded 1000 Å / min, and it was found that the phosphorus-doped polysilicon film could be polished at a higher polishing rate than the polishing compositions of Comparative Examples 1 to 8.
[0096] Furthermore, as shown in Table 1, when the polishing compositions of Examples 1 to 11 were used, the polishing rate for the TEOS film exceeded 40 Å / min, and the selectivity of the phosphorus-doped polysilicon film to the TEOS film was 19 or more. Compared to the polishing compositions of Comparative Examples 1 to 8, it was found that the polishing rate for the phosphorus-doped polysilicon film and the TEOS film was high, while the selectivity of the phosphorus-doped polysilicon film to the TEOS film was also high.
[0097] This shows that the polishing rate of an object to be polished is improved when the polishing composition contains, as abrasive grains, two types of silica particles having different silanol group densities.
Claims
1. A polishing composition comprising an abrasive grain and a dispersion medium, The abrasive grains have a silanol group density of 0 / nm 2 More than 4 / nm 2 and a first silica particle having a silanol group density of 4 / nm 2 More than 12 particles / nm 2 and second silica particles, The average secondary particle size of the first silica particles is smaller than the average secondary particle size of the second silica particles, A polishing composition having a pH of greater than 6.
2. 2. The polishing composition according to claim 1, wherein the first silica particles have an average secondary particle diameter of 10 nm or more and 200 nm or less, and the second silica particles have an average secondary particle diameter of 20 nm or more and 300 nm or less.
3. The silanol group density of the second silica particles is 5 / nm 2 More than 12 particles / nm 2 3. The polishing composition according to claim 1, wherein:
4. The silanol group density of the second silica particles is 6 / nm 2 More than 12 particles / nm 2 3. The polishing composition of claim 1, wherein:
5. 5. The polishing composition according to claim 1, further comprising at least one polishing rate enhancer selected from the group consisting of aminoethylpiperazine and ammonia.
6. The polishing composition according to any one of claims 1 to 5, having a pH of 7 or more.
7. The polishing composition according to any one of claims 1 to 6, further comprising a pH adjuster, wherein the pH adjuster comprises potassium hydroxide.
8. The polishing composition according to any one of claims 1 to 7, which is substantially free of an oxidizing agent.
9. The polishing composition according to any one of claims 1 to 8, which is used for polishing an object to be polished, which includes a polycrystalline silicon film doped with an n-type impurity.
10. The polishing composition according to claim 9, wherein the object to be polished further comprises at least one film selected from a silicon oxide film and a silicon nitride film.
11. A polishing method comprising a step of polishing an object to be polished, the object comprising a polycrystalline silicon film doped with an n-type impurity, with the polishing composition according to any one of claims 1 to 10.
12. A method for manufacturing a semiconductor substrate, comprising a step of polishing a semiconductor substrate including a polycrystalline silicon film doped with an n-type impurity by the polishing method according to claim 11.
Citation Information
Patent Citations
Polishing method
JP2007103515A
Polishing liquid for CMP, storage liquid for polishing liquid for CMP, polishing method, semiconductor substrate and electronic apparatus
JP2014022511A
Method for manufacturing polishing composition
JP2019057635A
Polishing composition, manufacturing method thereof, polishing method, and manufacturing method of semiconductor substrate
JP2020025066A
Elemental silicon polishing rate improver
JP2020155720A